Syntheses of Radioiodinated Pyrimidine-2,4,6-Triones as Potential Agents for Non-Invasive Imaging of Matrix Metalloproteinases - Hans-Jörg Breyholz; Klaus Kopka; Michael Schäfers; Stefan Wagner (MDPI AG, 2017)
Dysregulated expression or activation of matrix metalloproteinases (MMPs) is observed in many kinds of live-threatening diseases. Therefore, MMP imaging for example with radiolabelled MMP inhibitors (MMPIs) potentially represents a valuable tool for clinical diagnostics using non-invasive single photon emission computed tomography (SPECT) or positron emission tomography (PET) imaging. This work includes the organic chemical syntheses and in vitro evaluation of five iodinated barbiturate based MMPIs and the selection of derivative 9 for radiosyntheses of isotopologues [123I]9 potentially useful for MMP SPECT imaging and [124I]9 for MMP PET imaging.